Scientific research on graphene in the construction industry (state of the art) - Gutiérrez Orihuela, Kiara Nicole (2022)
This paper shows the results of descriptive research on graphene and its possibilities within the construction industry. To get into context, the construction industry is responsible for producing, exploiting and manipulating resources to build goods in modern cities (buildings, highways, sidewalks, airports, among others). Great challenges such as pollution and the excess of the resources used are observed, so this paper aims to explain why graphene is a good option to improve this industry. Among the results, graphene was found to be an innovative solution in the construction industry to reduce the cost of materials, environmental pollution through the FJH procurement method and increase the efficiency of the cement mix composition.